Concrete Block with Partial Replacement of Coarse Aggregate by Coconut Shell: A Review - Mokhtar, Mardiha; Zhen, Nge Zhuo; Jing, Chai Wei; Le, Lim Jia (Multidisciplinary Applied Research and Innovation, 2020)
Nowadays, the cost of construction materials is increasing day by day due to the increment in the prices of building materials. The main ingredient of concrete is cement, coarse aggregate, fine aggregate and water. Due to the quick development of the infrastructure development, the usage of the aggregates is increasing extremely, this situation has affected the environment and lead to ecological inequality. A lot of researchers have doing their research on the materials which can used to reduce the negative impact of concrete as well as increased the strength. Some waste materials such as fly ash, rice husk and slag are used in concrete according to their properties. In this research, the partially replacement of coconut shell as coarse aggregate was discussed based on the results from comprehensive review of literature. The coconut shells are a big problem for the disposal as it becomes useless after the usage of the coconut. Therefore, the partially replacement of coconut shell as coarse aggregate may help to reduce the cost of the construction and have the solution for the coconut shell disposal. The objective of this paper is to study and evaluate the published reviews that related to the physical characteristic of concrete that made by using coconut shells and to approach towards the feasibility of incorporating coconut shell as a replacement for coarse aggregate in concrete production. The recommendation is that the coconut shell able and suitable to use in lightweight aggregate to replace the conventional coarse aggregate. The partially replacement of coconut shell create a more economic concrete structure and leads to a sustainable development in construction field.